2017
DOI: 10.5398/medpet.2017.40.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Number of Gonadal Primordial Germ Cells (Gonadal PGCs) on the Stages of Early Embryonic Development of KUB Chicken

Abstract: Primordial germ cells (PGCs) are cells that will differentiate themselves into spermatogonia in the testis or oogonia in the ovary. Primordial germ cells arise from epiblast and circulate through the bloodstream and finally entering gonadal anlage. The aim of this study was to determine the number of gonadal PGCs of KUB chicken at different development stages. Sixty KUB chicken fertile eggs were divided into four groups (6, 7, 8, and 9 days incubation periods), and incubated at 38 o C with a humidity of 60%. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(38 reference statements)
0
2
0
3
Order By: Relevance
“…In contrast, there is limited information on the regulation of gene expression during the migration of PGCs in vivo. This is mainly because of the limited number of available PGCs [ 20 ]. The new technique for isolating viable avian PGCs combined with the method of RNA isolation from a single cell offers a unique approach for the study of cell transcriptome dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is limited information on the regulation of gene expression during the migration of PGCs in vivo. This is mainly because of the limited number of available PGCs [ 20 ]. The new technique for isolating viable avian PGCs combined with the method of RNA isolation from a single cell offers a unique approach for the study of cell transcriptome dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Szczerba et al [ 19 ] showed that the number of gPGCs was probably influenced by the stage of embryonic development. In the case of inbred lines or endangered breeds, the number of total PGCs seems to be lower compared to commercial chicken breeds [ 23 , 24 ]. This lower number of PGCs seems likely to be correlated with the lower productivity of the local chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Perbedaan ini kemungkinan disebabkan oleh perbedaan metode pemurnian sel dan perkembangan umur embiro. Jumlah PGC-gonad dipengaruhi oleh perkembangan embiro, dimana jumlah PGC-gonad secara signifikan meningkat dan mencapai puncaknya pada hari ke-7, karena PGC sebagian besar telah menetap di bagian gonad dan setelah itu jumlah PGC akan menurun (Sopiyana et al, 2017).…”
Section: Jumlah Selunclassified
“…Namun, dibandingkan dengan perolehan jumlah PGC-gonad ayam KUB pada umur embrio yang sama hanya mendapatkan jumlah PGC-gonad sebesar 113,7 sel per embrio (Sopiyana et al, 2017). Sementara itu, jumlah PGC-gonad ayam KUB yang dimurnikan dengan metode PBS (-) dengan waktu inkubasi embrio dalam PBS (-) selama 1 jam yaitu 151,47 sel per embrio pada umur embrio 7 hari (Kostaman dan Sopiyana, 2017).…”
Section: Jumlah Selunclassified
See 1 more Smart Citation